Simulation and sensitivity analysis of the heterogeneous oxidation of methane on a platinum foil - Behrendt, Frank; Deutschmann, Olaf; Maas, Ulrich; Warnatz, Jürgen (Journal of vacuum science & technology. A, Vacuum, surfaces, and films, 1995)
The heterogeneous oxidation of methane-air mixtures in a stagnation point flow onto a platinum foil is investigated numerically and results are compared with experiments. The analysis includes detailed reaction mechanisms for the gas phase as well as the surface. Gas‐phase transport and its coupling to the surface is described using detailed multicomponent models. The heterogeneous ignition, extinction, and autothermal behavior are interpreted in terms of elementary steps at the gas-surface interface. A sensitivity analysis of the surface reactions is performed to identify crucial steps in the mechanism, thus pointing to those reactions for which better kinetic and thermodynamic data are needed urgently.